Introduction to metallic nanoparticles - Vicky V Mody; Rodney Siwale; Ajay Singh; Hardik R Mody (Wolters Kluwer Medknow Publications, 2010)
Metallic nanoparticles have fascinated scientist for over a century and are now heavily utilized in biomedical sciences and engineering. They are a focus of interest because of their huge potential in nanotechnology. Today these materials can be synthesized and modified with various chemical functional groups which allow them to be conjugated with antibodies, ligands, and drugs of interest and thus opening a wide range of potential applications in biotechnology, magnetic separation, and preconcentration of target analytes, targeted drug delivery, and vehicles for gene and drug delivery and more importantly diagnostic imaging. Moreover, various imaging modalities have been developed over the period of time such as MRI, CT, PET, ultrasound, SERS, and optical imaging as an aid to image various disease states. These imaging modalities differ in both techniques and instrumentation and more importantly require a contrast agent with unique physiochemical properties. This led to the invention of various nanoparticulated contrast agent such as magnetic nanoparticles (Fe 3 O 4 ), gold, and silver nanoparticles for their application in these imaging modalities. In addition, to use various imaging techniques in tandem newer multifunctional nanoshells and nanocages have been developed. Thus in this review article, we aim to provide an introduction to magnetic nanoparticles (Fe 3 O 4 ), gold nanoparticles, nanoshells and nanocages, and silver nanoparticles followed by their synthesis, physiochemical properties, and citing some recent applications in the diagnostic imaging and therapy of cancer.